2019
DOI: 10.35971/jjhsr.v1i1.1795
|View full text |Cite
|
Sign up to set email alerts
|

Fakto- Faktor Yang Berhubungan Dengan Penggunaan Metode Kontrasepsi Jangka Panjang Wanita Usia Subur

Abstract: Banyak faktor yang mempengaruhi Penggunaan metode kontrasepsi jangka panjang antara lain pengetahuan, umur dan partisipasi suami. Berdasarkan data Dinas Kesehatan Kota Jambi didapatkan bahwa Puskesmas Paal V dengan jumlah PUS 7.220 orang, dengan KB aktif berjumlah 5.802 orang. Metode kontrasepsi jangka Panjang (MKJP) yang digunakan adalah Implant 3,01%, AKDR 9,5%, MOW 3,1%, dan MOP 0,3%. Sedangkang Non MKJP adalah suntik 60,1%, Pil 21,6% dan kondom 2,46%. Penelitian ini merupakan penelitian analitik dengan men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
1
2
0
20
Order By: Relevance
“…Despite of many benefits of long-term contraceptive method, the average percentage of total use of long-term contraceptive method in married women is still very small compared to the use of short-term contraceptive method (Aryati, et al, 2019). This is in accordance with the statement of Suryanti (2019) that most family planning participants on national scale used short-term contraceptive methods in the form of injections 29.0% and pills 12.1%.…”
Section: Introductionsupporting
confidence: 62%
“…Despite of many benefits of long-term contraceptive method, the average percentage of total use of long-term contraceptive method in married women is still very small compared to the use of short-term contraceptive method (Aryati, et al, 2019). This is in accordance with the statement of Suryanti (2019) that most family planning participants on national scale used short-term contraceptive methods in the form of injections 29.0% and pills 12.1%.…”
Section: Introductionsupporting
confidence: 62%
“…As getting older, the knowledge level and experience increases and this can provide a great opportunity to use long-term contraceptive methods such as the IUD. (Ethnic et al, 2018) According to Suryanti (2019), age affected a person's behavior in using contraceptives, older mothers have a smaller chance of using contraceptive methods than younger mothers. (Suryanti, 2019).…”
Section: Relationship Between Age and The Use Of Ltc Methodsmentioning
confidence: 99%
“…(Ethnic et al, 2018) According to Suryanti (2019), age affected a person's behavior in using contraceptives, older mothers have a smaller chance of using contraceptive methods than younger mothers. (Suryanti, 2019). Maternal age less than 30 years prefers short-term methods and over 35 years prefers LTC Method, this is often supported by reasons for using Family Planning such as because of the number of children (Christiani et al, 2013) The author concluded that a woman's age will affect her desire to have the number of children, young women tend to have more children than old age, thus preferring the Non-LTC method.…”
Section: Relationship Between Age and The Use Of Ltc Methodsmentioning
confidence: 99%
“…6 Jumlah peserta KB secara nasional berdasarkan pemilihan dalam pemakaian alat kontrasepsi terbanyak dipakai di antaranya ialah alat kontrasepsi suntik 29,0%, pil 12,1%, implant 4,7%, alat dalam rahim 4,7%, metode operasi wanita (MOW) 3,8%, kondom 2,5%, dan metode operasi pria (MOP) 0,2%. 7 Secara nasional program KB di Indonesia lebih diarahkan pada penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) dibandingkan Non Metode Kontrasepsi Jangka Panjang (NonMKJP) Sementara itu, Survei Sosial Ekonomi Nasional tahun 2012 (Susenas, 2012) memperlihatkan data penggunaan alat kontrasepsi Provinsi Jawa Timur menunjukkan masih didominasi oleh Non-MKJP dibandingkan penggunaan MKJP. 8 Masyarakat diharapkan dapat memiliki pengetahuan mengenai pentingnya untuk mengikuti program keluarga berencana (KB) terutama Pasangan Usia Subur (PUS) yang dapat berpengaruh pada kondisi pertumbuhan penduduk di Indonesia.…”
unclassified